2016
DOI: 10.1515/jpem-2015-0107
|View full text |Cite
|
Sign up to set email alerts
|

Urinary myo-inositol levels in Japanese schoolchildren with normal glucose tolerance

Abstract: These studies demonstrated the normal range of UMI in children and possibility of a novel biomarker for early detection of glucose intolerance in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In contrast, the DUMI test requires no blood collection, but involves the loading of 75 g of glucose, resulting in a burden on the examinees. In this regard, Takakado et al reported that UMI levels from urine samples selfcollected at home were closely associated with blood glucose parameters obtained from a 75-g OGTT test meal loading at home, focusing on the high stability of MI in urine at room temperature 15 . Although further study is necessary, the UMI test can be carried out with urine and, therefore, performed at home using test meals on a separate day from the date of a health checkup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the DUMI test requires no blood collection, but involves the loading of 75 g of glucose, resulting in a burden on the examinees. In this regard, Takakado et al reported that UMI levels from urine samples selfcollected at home were closely associated with blood glucose parameters obtained from a 75-g OGTT test meal loading at home, focusing on the high stability of MI in urine at room temperature 15 . Although further study is necessary, the UMI test can be carried out with urine and, therefore, performed at home using test meals on a separate day from the date of a health checkup.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary MI (UMI) is known to increase with a decrease in glucose tolerance in the order of healthy individuals, prediabetes, IGT and diabetes, and it is known that the determination of ΔUMI, the difference between UMI before glucose loading and UMI 120 min after glucose loading during the 75‐g OGTT, is useful for identifying patients at high risk of diabetes 12 , 13 , 14 , 15 . We studied the participants with FPG levels of 100–125 mg/dL, and developed the cut‐off value of 10 mg/g Cre to detect glucose intolerance with the sensitivity of 93% for diabetes and 68% for IGT 16 .…”
Section: Introductionmentioning
confidence: 99%